Bezdomność w świetle orzecznictwa sądów administracyjnych – wybrane aspekty - Mędrzycki, Radosław (Kwartalnik Prawa Publicznego, 2013)
Social assistance in Poland is regulated by the Law of 12 March 2004 on Social Assistance. In this paper author analyzes the basic problems of this regulation relating to help of homelessness which appears in judgments of polish administrative courts. The biggest issue in judgments is deeming person for homeless. Many of judgments show a need of cooperation between homeless and social workers. In author’s opinion, social assistance ought to security of dignity of the homeless person. The judgments of polish administrative courts have a big influence on it. Nowadays, besides the legislative and executive, judicial power creates standard of help of homeless.